Evaluation Method of Bonding To Root Canal Dentin After Sodium Hypochlorite Treatment - Alaa M. El Araby (Journal of the Dow University of Health Sciences, 2011)
Statement of the problem: Shear bond strength test is a common test to evaluate the bond between restorative materials and tooth structure but it cannot measure the marginal adaptation of the restorative filling materials. Therefore, in this research an evaluation method of punch out test was employed to evaluate resin bonding to root canal wall dentin by measuring both marginal adaptation and shear bond strength simultaneously. Objectives: The aim of this study is to investigate the reliability and efficiency of punch out shear test to evaluate the effect of sodium hypochlorite (NaOCl) as a root canal irrigant on composite resin bonding to canal dentin and also to evaluate the contraction gap formation from the same specimen. The null hypothesis tested was that treatment of root canal with NaOCl would not compromise bonding to root canal dentin, whether a total etching adhesive or self-etching adhesive was used. Materials and Methods: A total etching adhesive system (Optibond Solo Plus) and a self etching adhesive system (XenoIII) were employed in this study. A standardized truncated cone cavity (4 mm in base diameter, 3 mm in depth and a convergence angle of 5Â° ), was prepared at the top portion of the root canal. The cavities were subjected to sodium hypochlorite treatment for different periods of time and then rinsed with distilled water. Then, one of the aforementioned dentin bonding systems was applied to the cavity walls according to the manufacturer's instructions. The cavities were then filled with a micro-hybrid composite resin. Results and conclusion: The increase in the NaOCl application time resulted in a progressive decrease in the punch out shear bond strength for the specimens treated with a self etching adhesive system. A marginal gap was detected when XenoIII was applied after NaOCl application.